2008
DOI: 10.1016/j.jembe.2007.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Top-down and bottom-up control of infauna varies across the saltmarsh landscape

Abstract: Responses of infaunal saltmarsh benthic invertebrates to whole-ecosystem fertilization and predator removal were quantified in Plum Island Estuary, Massachusetts, USA. Throughout a growing season, we enriched an experimental creek on each flooding tide to 70 µM NO 3 -and 4µM PO 4 -3 (a 10 x increase in loading above background), and we reduced Fundulus heteroclitus density by 60% in a branch of the fertilized and a reference creek. Macroinfauna and meiofauna were sampled in creek (mudflat and creek wall), mars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 76 publications
3
30
0
Order By: Relevance
“…Lewis & Eby (2002) investigated the spatial patterns of gastropods (periwinkle snails) and blue crab, their predators, along the edge of a North Carolina (USA) Spartina alterniflora marsh and found that pursuant to the concept of increased inhibition of crab foraging with increasing distances into dense S. alterniflora marsh, snail densities increased positively with increased distance from the marsh edge. Although responses were found to be highly taxa specific, Fleeger et al (2008) also found that marsh edge (as well as adjacent tidal channel wall) exhibited the strongest response by invertebrates to experimental predator removal and nutrient additions.…”
Section: Edge Effectsmentioning
confidence: 85%
“…Lewis & Eby (2002) investigated the spatial patterns of gastropods (periwinkle snails) and blue crab, their predators, along the edge of a North Carolina (USA) Spartina alterniflora marsh and found that pursuant to the concept of increased inhibition of crab foraging with increasing distances into dense S. alterniflora marsh, snail densities increased positively with increased distance from the marsh edge. Although responses were found to be highly taxa specific, Fleeger et al (2008) also found that marsh edge (as well as adjacent tidal channel wall) exhibited the strongest response by invertebrates to experimental predator removal and nutrient additions.…”
Section: Edge Effectsmentioning
confidence: 85%
“…A total of 19 species of annelids and 38 species of copepods were found in quantitative studies across 41 Mar Ecol Prog Ser 359: 37-49, 2008 habitats in PIE (Johnson et al 2007, Fleeger et al 2008. Isotope analyses were conducted on the more abundant infaunal species, including the annelids Nereis diversicolor (mudflat and creek wall), Streblospio benedicti (mudflat), Paranais litoralis (mudflat, Spartina alterniflora and S. patens understories), Manayunkia aestuarina (creek wall, S. alterniflora and S. patens understories), Fabricia sabella and Pygospio elegans (both creek wall), and the abundant harpacticoid copepod Heterolaophonte sp.…”
Section: Resultsmentioning
confidence: 99%
“…Meiofaunal communities are dominated by nematodes and harpacticoid copepods (Fleeger et al 2008). Potential predators on infauna include the killifish Fundulus heteroclitus, the green crab Carcinus maenas and the grass shrimp Palaemonetes pugio (Deegan et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of ecological stressors vary across the salt marsh landscape (Fleeger et al 2008). Duration of tidal inundation (i.e., relative intertidal elevation) is a key factor determining infaunal and epifaunal community changes across the marsh landscape, and also controls intertidal access for nekton.…”
Section: Faunamentioning
confidence: 99%